Awareness of Yoga and Its Benefit Among Medical Students of Tertiary Care Teaching Hospital in Birgunj - Shrestha, Esha; Shreshtha, Ripti; Ghimire, Dayaram; Aryal, Vibina (Med Phoenix, 2022)
Introduction Yoga is a practice of mind and body that combines physical postures, breathing exercises, and meditation. Yoga helps reduce stress, lower blood pressure and heart rate. It is considered one of many complementary and integrative health approaches. Yoga brings together physical and mental discipline that may help achieve a healthy body and peaceful mind. In this study, we aim to assess knowledge and awareness regarding yoga and its benefit among preclinical students. Materials and Methods This cross-sectional study includes 176 preclinical medical students of National Medical College, Birgunj, Nepal. A total of 14 self-designed close-ended questionnaires regarding knowledge and awareness about Yoga were used as a study tool. Data analysis was done using Microsoft Excel, 2010. Results Among 176 preclinical students, 77.84% had the habit of practicing yoga, but only 14.20% of students continued it. About 96.59% of students knew the benefits of yoga. Conclusion The result of the study reveals that there is a positive influence of practicing yoga among students. By practicing yoga, it is capable to achieve personal abilities such as stress management, attention in their work, and maintenance of physical and mental health.